ANALYSIS OF THE EFFECTIVENESS OF THE PERSONNEL ADMINISTRATION INFORMATION SYSTEM IN SUPPORTING EMPLOYEE PERFORMANCE AT THE MORO'O DISTRICT OFFICE OF WEST NIAS DISTRICT - Vivi Kristiani Gulo; Syah Abadi Mendrofa; Robin Markus Putra Waruwu; Dedi Irawan Zebua (LPPM YPITI, 2026)
This research is entitled